(untitled) (International Journal of Nursing Education, 2023)
Subjective well-being is essential for adolescents as it affects their social relationships, learning processes, and emotions. Adolescents who have low SWB quickly feel anxious, depressed, and anxious. This study aims to determine the relationship between subjective well-being and social support for adolescents in an Islamic boarding school in Aceh province, Indonesia. This study applied a cross-sectional design involving 169 adolescents living in an Islamic Boarding School in the Aceh province of Indonesia. Data were collected using the Multidimensional Scale of Perceived Social Support (MSPSS), the Scale of Positive and Negative Experience (SPANE), and the Satisfaction with Life Scale (SWLS). The Chi-square test showed a relationship between social support and adolescent subjective well-being (p-value 0.030). Therefore, social support should be considered as an aspect which is needed to be improved to affect subjective well-being among adolescents.